Legal Protection for Child Victims of Sexual Violence Its Relationship with the Child Protection Law and the Convention on the Rights of the Child - Eva Dwi Dayati; Alef Musyahadah Rahmah; Setya Wahyudi; Dwi Hapsari Retnaningrum (LPPM Universitas Harapan Bangsa, 2026)
Children are a group that is highly vulnerable to becoming victims of violence, especially sexual violence. Sexual violence against children is a serious crime that has a broad impact, especially on the future of children as the next generation of the nation. Legal protection is a state policy to protect, fulfill, and guarantee the fulfillment of children's rights and obligations in the context of law enforcement for the protection of children. This study aims to examine the legal protection provisions for child victims of sexual violence in Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection and its compatibility with the principles of the Convention on the Rights of the Child (CRC). The method used in this study is normative juridical and the data used is secondary data. The results of the study show that the child protection law has provided a legal basis for child victims of sexual violence and that the protection provided is in accordance with the principles set out in CRC. In this case, strengthening the monitoring mechanism is very important so that regulations on the protection of child victims of sexual violence can be implemented effectively and in the interests of the victims.